Management of traumatic tympanic membrane perforation: a comparative study - Gao, Tianxi (Ther Clin Risk Manag, 2017)
This prospective study was conducted to evaluate the efficacy of sea buckthorn oil patches in treating traumatic tympanic membrane (TM) perforations. We enrolled 370 patients with traumatic TM perforations of different sizes. These patients were randomly assigned to control group and treatment group. In the treatment group, a sterile cotton patch with sea buckthorn oil was used to cover the TM perforations. In the control group, patients were treated with a sterile cotton patch. The healing rate and time were compared between the two groups. We found that the overall healing rate was significantly higher in the treatment group than in the control group. For middle and large TM perforations, sea buckthorn oil treatment led to a significant increase in the healing rate. At 2 months after injury, the duration of healing was, generally, shorter in the treatment group than in the control group (P<0.05). In conclusion, sea buckthorn oil patches are effective in treating middle and large TM perforations, which results in increased healing rates and decreased healing time.